Both synergism and interaction diversity explain the mixtures of defensive monoterpenes in spruce oleoresin - Zaman, Rashaduz; Jain, Akanksha; Hammerbacher, Almuth; Gershenzon, Jonathan; Kandasamy, Dineshkumar ; 0000-0002-5450-3231 (Functional Ecology, 2025)
Chemical defences, such as the monoterpenes of conifer oleoresin, frequently occur as complex blends of many components, but the selective pressures that maintain these mixtures are not yet known. Several theories attempt to explain the existence of chemical defence mixtures in plants. However, due to limited empirical evidence, it is unclear which theories might best apply. Here, we tested the vapour phase activity of 12 individual Norway spruce monoterpenes and their naturally occurring mixtures to two types of natural spruce enemies, the adult Eurasian spruce bark beetles, Ips typographus, and their three major symbiotic fungi, using survival and growth bioassays. Next, we evaluated whether spruce trees could alter their monoterpene profile in response to fungal infection. Individual monoterpenes had generally opposite effects on bark beetles compared to symbiotic fungi. The compounds that were most toxic to beetles were the least inhibitory to fungal growth and vice versa. The least abundant monoterpenes had the strongest activity against beetles or fungi, while the most abundant monoterpenes showed intermediate activity against both groups of enemies. Additionally, the activity of monoterpene mixtures was significantly stronger against beetles and some symbiotic fungi than the additive effects of individual compounds. Among the symbiotic fungi tested, one (Grosmannia penicillata) exhibited high tolerance to monoterpenes, and its growth was even stimulated by the monoterpenes most toxic to the beetle. Interestingly, spruce bark responded to G. penicillata inoculation by accumulating higher concentrations of specifically fungistatic monoterpenes. Our results support the predictions of the interaction diversity hypothesis, which posits that defence mixtures are maintained in plants because the individual components target different attackers, as well as the synergy hypothesis, which predicts that mixtures will exhibit stronger activity than single compounds. Thus, these two theories may deserve increased emphasis in explaining the widespread occurrence of mixtures in plant chemical defence. Read the free Plain Language Summary for this article on the Journal blog.
Publisher Copyright: © 2025 The Author(s). Functional Ecology published by John Wiley & Sons Ltd on behalf of British Ecological Society.
Keywords: chemical mixtures; interaction diversity; inverse toxicity; monoterpene toxicity; Norway spruce; ophiostomatoid fungi; spruce bark beetle